Maternal Folic Acid and Risk of Childhood Autism - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers from the Norwegian Institute of Public Health, Oslo; Institute of Child Health, London, UK; and other centers in Norway, UK, and the US examined the association between maternal use of prenatal folic acid supplements (4 weeks before to 8 weeks after start of pregnancy) and risk of autistic spectrum disorders in children derived from the population-based, prospective Norwegian Mother and Child Cohort Study (MoBa).